2014
DOI: 10.1111/ppl.12278
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and antioxidant responses of two accessions of Arabidopsis thaliana in different light and temperature conditions

Abstract: During their lifetime, plants need to adapt to a changing environment, including light and temperature. To understand how these factors influence plant growth, we investigated the physiological and antioxidant responses of two Arabidopsis accessions, Shahdara (Sha) from the Shahdara valley (Tajikistan, Central Asia) in a mountainous area and Lovvik-5 (Lov-5) from northern Sweden to different light and temperature conditions. These accessions originate from different latitudes and have different life strategies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…In contrast to the present results, recent studies of vte1‐vte5 gene expression analysis in a variety of Arabidopsis accessions (Szymańska et al . ) showed that the most activated was the vte3 gene, both under LL and HL. However, it seems that the growth conditions applied in those studies were not causing oxidative stress, as revealed in the data of prenyllipid analysis, where nothing much differences in their content were observed between the LL‐ and HL‐grown plants.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to the present results, recent studies of vte1‐vte5 gene expression analysis in a variety of Arabidopsis accessions (Szymańska et al . ) showed that the most activated was the vte3 gene, both under LL and HL. However, it seems that the growth conditions applied in those studies were not causing oxidative stress, as revealed in the data of prenyllipid analysis, where nothing much differences in their content were observed between the LL‐ and HL‐grown plants.…”
Section: Discussionmentioning
confidence: 97%
“…We demonstrated that both accessions grew better in the HL conditions and at the lower temperature (16°C) than in LL and at 23°C. Although we did not show differences in prenyllipid levels (including tocochromanols) we found variation in the vte genes expression levels (Szymanska et al ).…”
Section: Discussionmentioning
confidence: 50%
“…In this study, we tried to find correlation between light intensity, growth temperature, tocochromanol response and climate parameters of the origin of the accessions. The present research was stimulated by the results of previous experiments (Szymanska et al ) in which we compared two accessions for their antioxidant and physiological response to the light and the temperature changes. Those accessions (Lov‐5 and Sha) originate from two distinct places and show different life strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among Arabidopsis accessions, there is substantial natural variation in drought-related traits such as water use efficiency, growth, gene expression, Pro accumulation, ABA accumulation, and others (Des Lasky et al, 2014;Lovell et al, 2015;Bac-Molenaar et al, 2016;Mojica et al, 2016;Kalladan et al, 2017). The Shahdara accession (Sha; also referred to as Shakdara) differs from commonly used reference accessions such as Columbia (Col) and Landsberg erecta (Ler) in many traits, in particular, drought-related traits (Loudet et al, 2002;Bouchabke et al, 2008;Ren et al, 2010;Vallejo et al, 2010;Jasinski et al, 2012;Kesari et al, 2012;Pineau et al, 2012;Angelovici et al, 2013;Sharma et al, 2013;Szyma nska et al, 2015). The type of local environment that Sha is adapted to, as well as whether Sha should be considered more or less drought tolerant than other accessions, are unclear (Trontin et al, 2011).…”
mentioning
confidence: 99%